CULTURAL IMPACT TO THE CIRCUMCISION OF FEMALE CHILDREN IN INDONESIA - Raudhatun Nuzul ZA (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Circumcisions of the female children are done for 0 – 18 years old in Indonesia, depending on the local culture.   The female circumcision generally is done to the baby after birth, 70 % is in Java and Madura, 78 % is in North Sumatra and 64% is in West Sumatra, are executed to under 1 year old and partly 7 – 9 years old.In the Middle East and Asian community, the circumcision practices are estimated to be carried out to more than 2 million female children. Some female children are carried out the circumcision when they were still babies, on 7 – 10 years old, and other communities also carry out after delivering the first baby.In the circumcision practice to the female babies in Indonesia, the doctor or midwife generally only take off the praeputiummembrane. It is the membrane that wraps or covers the clitoris. Circumcision Practice of the female has become the tradition of the particular communities. The main purpose is to control the sexual libido of the women.  There is an assumption that the dirt on the clitoris can cause the women sexual libido become uncontrollable, whereas the circumcision practice is harmful to physical health and sexualpsychic of the women.                       Keywords: Culture, Circumcision of female children